Recent Advances in N-O Bond Cleavage of Oximes and Hydroxylamines to Construct N-Heterocycle - Hui-Min Jiang; Yi-Lin Zhao; Qing Sun; Xuan-Hui Ouyang; Jin-Heng Li (Molecules, 2023)
Oximes and hydroxylamines are a very important class of skeletons that not only widely exist in natural products and drug molecules, but also a class of synthon, which have been widely used in industrial production. Due to weak N-O σ bonds of oximes and hydroxylamines, they can be easily transformed into other functional groups by N-O bond cleavage. Therefore, the synthesis of N-heterocycle by using oximes and hydroxylamines as nitrogen sources has attracted wide attention. Recent advances for the synthesis of N-heterocycle through transition-metal-catalyzed and radical-mediated cyclization classified by the type of nitrogen sources and rings are summarized. In this paper, the recent advances in the N-O bond cleavage of oximes and hydroxylamines are reviewed. We hope that this review provides a new perspective on this field, and also provides a reference to develop environmentally friendly and sustainable methods.